Literacy Culture Assistance on Children Through Rumah Belajar Ilalang in Tahunan, Jepara - Ulin Nihayah (Universitas Islam Negeri Walisongo Semarang, 2022)
Reading is a culture that is almost degraded nowadays; even the culture of reading through books has become extinct, replaced by watching gadgets. The revitalization of literacy culture is certainly not easy in the midst of rapidly developing technology. TBM (Community Reading Park) Weed Learning House (RBI) bridges the literacy revitalization process for children in Tahunan, Jepara. The research was carried out through participatory service involving students of UIN Walisongo who were gathered in the Programmed Initiative KKN Mandiri program as a form of student anxiety about the decline in children's interest in reading. The mentoring activities resulted in the realization of reading culture assistance for children through the active RBI TBM by holding Mbelik Mili, Friday Familiar, and Sunday reading. In addition, efforts to improve literacy culture have resulted in the continuous development of RBI assistance because there is an interest in literacy in children by creating a reading culture, continuous development of mentoring in RBI through the government and stakeholders in Jepara, the need for the development of adequate facilities in TBM RBI, the need for stakeholder support holders in the community.